Evolution of transcriptional enhancers and animal diversity - Silva Junqueira de Souza, Flavio (2013)
Deciphering the genetic bases that drive animal diversity is one of the major challenges of modern biology. Although four decades ago it was proposed that animal evolution was mainly driven by changes in cis-regulatory DNA elements controlling gene expression rather than in protein-coding sequences, only now are powerful bioinformatics and experimental approaches available to accelerate studies into how the evolution of transcriptional enhancers contributes to novel forms and functions. In the introduction to this Theme Issue, we start by defining the general properties of transcriptional enhancers, such as modularity and the coexistence of tight sequence conservation with transcription factor-binding site shuffling as different mechanisms that maintain the enhancer grammar over evolutionary time. We discuss past and current methods used to identify cell-type-specific enhancers and provide examples of how enhancers originate de novo, change and are lost in particular lineages. We then focus in the central part of this Theme Issue on analysing examples of how the molecular evolution of enhancers may change form and function. Throughout this introduction, we present the main findings of the articles, reviews and perspectives contributed to this Theme Issue that together illustrate some of the great advances and current frontiers in the field.